Particular Aspects Of The Concept Of “Terrorism” - Popov , Volodymyr; Hermanov, Dmytro; Perepelytsia, Sergii (Archives of Criminology and Forensic Sciences, 2022)
The research paper studies current issues and prospects for the formation and implementation of the state policy of combating terrorism. As the author emphasizes, terrorist acts related to the of weapons, munitions or explosives are defined as the most dangerous and destructive consequences, as they pose a real threat to people’s lives and health, and cause the destruction of industrial, economic, or defense facilities. It became especially relevant during the resistance of the Ukrainian people to armed aggression by Russia. Therefore, the relevance of the theoretical and methodological development of particular issues of the concept of “terrorism” is beyond doubt and is the purpose of writing this research paper. The most characteristic features of modern terrorist activity should be considered to be its mostly organized nature, ideological cover for political or self-interested motivation, financing and coordination by non-governmental organizations, representatives of criminal communities or individual states, as well as the use by terrorists of corrupt connections with representatives of state authorities, law enforcement officers, employees of special services of foreign countries and influential persons of the economic and financial segment.